Sorting-sorting-procedure-free short-process application method for waste refractory materials

Through a short-process application method that does not require picking and sorting, the used carbon-containing lining mixed with waste refractory materials in the ladle is directly used to prepare converter repair bricks, which solves the problem of recycling and reuse of waste refractory materials and achieves high efficiency and Low-cost resource recycling and environmental protection.

CN119330731APending Publication Date: 2025-01-21ANGANG VESUVIUS REFRACTORY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411566433.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively recycle and reuse waste refractory materials, resulting in waste of resources and environmental pollution, and the recycling process is complex, high cost, and low market response.

Method used

Using a short-process application method without picking and sorting process, the used carbon-containing lining of the ladle is mixed with waste refractory materials. After homogenization and crushing, it is directly used to prepare converter repair bricks without removing waste residue impurities at all.

Benefits of technology

It has achieved 100% recycling and reuse of waste refractory materials, reduced labor intensity and costs, improved work efficiency, and produced magnesium- and carbon-containing mending bricks for converter bottom mending with excellent use effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a short-process application method of a waste refractory material without a sorting process, which is characterized in that a carbon-containing lining refractory material used by a steel ladle is directly used for preparing a converter fettling brick after being homogenized and crushed without the sorting process and without removing waste residue impurities. According to the invention, the carbon-containing steel ladle post-mixed refractory material which is not sorted and classified, does not remove waste residue impurities and is completely recovered is adopted for preparing the steel smelting converter fettling material, the magnesium-containing carbon-containing fettling brick for converter bottom fettling with excellent use effect can be produced, and the requirement of steel smelting is completely met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of refractory materials, and in particular to a short-process application method of waste refractory materials without sorting and separation processes, which is used for preparing steel smelting converter repair materials. Background Art

[0002] With the vigorous development of high-temperature industry, the consumption of refractory materials has also increased significantly. According to statistics, the total consumption of refractory materials in China in 2022 will exceed 19 million tons, and the solid waste of refractory materials generated will reach 10 million tons. In this way, the consumption ratio of refractory materials is about 50%, and the remaining 50% becomes solid waste materials, but the recycling rate of such solid waste materials is extremely low, only 20-40%. The vast majority of refractory waste materials are landfilled as industrial waste, which not only pollutes the environment but also wastes resources. In comparison, some countries and regions, due to resource and other reasons, have recycled and reused discarded refractory solid waste materials relatively early, and their recycling rate is as high as 60%. Therefore, studying the recycling and reuse of discarded refractory materials can reduce the mining of refractory minerals in my country, reduce the production costs and energy consumption of the preparation process, and has important economic benefits and social significance.

[0003] At present, the common treatment methods for used refractory materials are shown in Table 1:

[0004] Table 1

[0005]

[0006]

[0007] At present, the difficulties in recycling and reusing used refractory materials are mainly in the following aspects: 1. Technical difficulties - the key technologies for high-value utilization of refractory solid waste, including waste classification and recycling technology, biodegradation technology, pyrolysis and gasification technology, etc., require a lot of research and development and experimental work to solve. At the same time, if the investment and manufacturing become complicated, the cost performance will be lost, and the market will be difficult to respond; 2. Restrictions on use conditions - due to the wide variety of refractory solid waste and complex use conditions, the use of some solid waste is subject to certain restrictions. For example, some types of solid waste may require specific treatment processes or equipment to use; 3. Chaotic recycling management - currently, there is chaos in the recycling management of refractory solid waste, lack of unified management and norms, which leads to problems such as low recycling efficiency, waste of resources and environmental pollution.

[0008] In summary, except for 20-40% of the used refractory materials in my country that are recycled and reused, nearly two-thirds of the used refractory materials cannot be effectively recycled. The main reasons are: 1. A large part of them are medium and low-end used refractory materials, and the price of new products is not high. If a large amount of selection, manufacturing and processing costs are invested in used refractory materials, the cost is likely to be higher than the price of new products, and the enthusiasm of both parties in the market is not high; 2. Due to the reasons for the site where the refractory materials are used and the degree of user cooperation, most of the used refractory materials have not been effectively and accurately classified and recycled. They are basically mixed and need to be sorted manually in the later stage, which is inefficient and not accurate. For example, the magnesium-aluminum-carbon bricks, aluminum-magnesium-carbon bricks, and magnesium-carbon bricks used in the ladle are all black in appearance and used in different parts of the ladle. Most of the time, they are mixed after dismantling. If you do not have many years of picking experience and observe the cross-section of the bricks, it is difficult to distinguish them correctly. Because there is no effective classification, it directly affects the next step of recycling and reuse; 3. Some local governments lack strategic understanding of mineral resources, are greedy for short-term results, and do not have strict and scientific planning for the reasonable control and mining of local mineral resources, resulting in low prices for new mineral raw materials and difficulty in developing the recycling of used refractory materials. Summary of the invention

[0009] The present invention provides a short-process application method for waste refractory materials without sorting and sorting procedures, which 100% adopts all recycled carbon-containing mixed refractory materials used for ladle use without sorting and classification and without removing waste slag impurities, and is used to prepare steel smelting converter repair materials. It can produce magnesium-containing and carbon-containing repair bricks for converter bottom repair with excellent use effect, which fully meet the needs of steel smelting.

[0010] In order to achieve the above object, the present invention adopts the following technical solutions:

[0011] A short-process application method for waste refractory materials without a sorting and separation process. The method is to directly use the carbon-containing lining refractory materials used in the ladle for preparing converter repair bricks after homogenization and crushing without going through a sorting and separation process and without removing waste slag impurities.

[0012] Specific methods include:

[0013] 1) Remove the carbon lining refractory materials from the steel package without sorting or separation, and mix and store them all before homogenizing;

[0014] 2) crushing the mixed waste refractory material homogenized in step 1), crushing a part into particles less than 10 mm as aggregate, and grinding a part into 180 mesh powder;

[0015] 3) The granular aggregate of less than 10 mm is mixed at a ratio of 70wt% to 80wt%, the powder of 180 mesh is mixed at a ratio of 20wt% to 30wt%, and an anhydrous taphole binder is added at a ratio of 3wt% to 6wt% of the total amount of the aggregate and the powder;

[0016] 4) First, dry mix the aggregate and powder for 2 to 5 minutes, then add the anhydrous taphole mud binder at one time, wet mix for 5 to 10 minutes, and then discharge the material;

[0017] 5) Pressing the mixture obtained in step 4) into bricks.

[0018] Random sampling of the homogenized mixed waste refractory materials was performed, and the chemical indicators were as follows: MgO: 40% to 65%, Al 2 O 3 :20%~45%, SiO 2 : 5%~15%, CaO: 3%~10%, C: 3%~5%, Fe: 0~5%; other impurities include Fe 2 O 3 、MnO.

[0019] The method for pressing into bricks in step 5) comprises: the pressed bricks are allowed to stand for 8 to 16 hours, dried in a drying kiln heated by electricity or gas hot air, the door is closed after entering the kiln, the temperature is raised from room temperature by 20 to 30°C per hour to 120 to 150°C, the highest temperature is kept for 4 to 6 hours, the fire is turned off, and the bricks are cooled to below 80°C before being taken out of the kiln, selected and packaged, and stored for shipment.

[0020] The physical and chemical indicators of the anhydrous taphole mud binder are: anthracene oil greater than 50wt%, asphalt greater than 10wt%; specific gravity greater than 1.35.

[0021] The physical indicators of the furnace repair bricks are: room temperature compressive strength greater than 20MPa, room temperature flexural strength greater than 5MPa, and bulk density greater than 2.2g / cm 3 ; Chemical indicators: MgO: 40%~65%, Al 2 O 3 :20%~45%, SiO 2 : 5%~15%, CaO: 3%~10%, C: 3%~5%, Fe: 0~5%; other impurities include Fe 2 O 3 、MnO.

[0022] The dimensions of the converter repair bricks are 200-300 mm in length, 80-150 mm in width and 50-100 mm in height.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] The present invention adopts all the carbon-containing lining mixed waste refractory materials used in the ladle according to the physical and chemical indicators and usage characteristics required by the actual use of magnesium-containing carbon-containing furnace bricks for converter bottom repair. The mixed waste refractory materials do not need to be classified and sorted, which greatly reduces the difficulty of recycling the waste refractory materials and greatly improves the recovery and reuse ratio of the waste refractory materials.

[0025] At present, all the waste refractory materials for recycling and reuse are the waste refractory materials removed by users. A large amount of manpower and material resources are arranged in advance for sorting according to the types of magnesia carbon bricks, magnesia aluminum carbon bricks, aluminum magnesium carbon bricks, magnesia chrome bricks, chrome-free bricks, burned magnesia bricks, iron ditch castables, skateboards, etc. The result is low efficiency, extremely high cost, low picking accuracy, poor working environment and safety. The actual situation is that most waste refractory materials have no chance and are unlikely to be accurately classified, which has caused nearly two-thirds of the waste refractory materials to be unable to be recycled and reused. On the one hand, it pollutes the environment, and on the other hand, it is forced to use raw materials and minerals such as dead-burned magnesia, fused magnesia, magnesite, dolomite, etc., which greatly wastes precious natural resources.

[0026] The innovation of the present invention is that, through evaluating the indicators of used carbon-containing lining mixed waste refractory materials of ladle and evaluating the process environment of converter repair, the used carbon-containing lining mixed waste refractory materials of ladle are only simply homogenized without sorting, and all are mixed for secondary use. Not only 100% of the used carbon-containing lining mixed waste refractory materials of ladle are used, achieving the purpose of recycling and reusing all waste refractory materials, but also the process of sorting and sorting is avoided, labor intensity is reduced, work efficiency is improved, and the magnesium-containing carbon-containing repair bricks for converter bottom repair prepared by the method of the present invention have excellent use effect.

[0027] The present invention adopts a very simple manufacturing process, with extremely low cost and energy consumption and extremely high cost performance.

[0028] The present invention utilizes 100% of the used carbon-containing lining mixed waste refractory materials of the ladle without any sorting and separation process, wherein the slag and metamorphic layer attached to the waste refractory materials are also reused as furnace repair materials, which not only saves resources but also greatly reduces the sorting cost. The most important thing is that the new furnace repair bricks have greatly improved sintering performance due to the presence of slag and metamorphic layer, which greatly improves the furnace repair effect of the converter furnace repair bricks. DETAILED DESCRIPTION

[0029] The specific implementation modes of the present invention are further described below in conjunction with examples. The following examples are used to specifically illustrate the contents of the present invention. These examples are only general descriptions of the contents of the present invention and do not limit the contents of the present invention.

[0030] The novel magnesium-containing carbon-containing furnace bricks for the bottom repair of the converter of the present invention are 100% made of carbon-containing mixed refractory materials after the use of the ladle that have not been accurately classified and recycled through optimized design, including: used slag line waste magnesium carbon bricks, ladle bottom waste aluminum magnesium carbon bricks, ladle wall waste magnesium aluminum carbon bricks, waste fire mud, waste steel slag, various refractory metamorphic layers, etc., through the optimization design of the ingredients and the use of a very simple manufacturing process, to produce high-quality magnesium-containing carbon-containing furnace bricks for the bottom repair of the converter. For the first time, the steel slag and metamorphic layers attached to the surface of the waste refractory materials are not sorted or removed, but added as sintering agent materials, and all are mixed for secondary use, which greatly improves the repair effect of the converter furnace bricks. The binder part of the present invention adopts a very common anthracene oil and asphalt mixture, that is, the binder of conventional blast furnace anhydrous cannon mud, to produce magnesium-containing carbon-containing furnace bricks for the bottom repair of the converter with the same excellent use effect, which fully meets the needs of steel smelting.

[0031] The present invention is achieved through the following technical solutions:

[0032] The novel magnesium-carbon bricks for converter bottom repair are composed of the following raw materials in weight percentage: 70% to 80% of mixed magnesium-carbon granular aggregate 10-0mm, 20% to 30% of mixed magnesium-carbon material fine powder 180 mesh, and 3% to 6% of anhydrous taphole binder accounting for the total amount of mixed magnesium-carbon material.

[0033] The production method is:

[0034] First, remove the carbon steel ladle and mix the used refractory materials for simple homogenization. Specifically: according to the amount of used refractory materials to be homogenized, use a forklift to shovel out the mixed used refractory materials one by one on a flat site, and stack them layer by layer again. Repeat this process 5-7 times to achieve the purpose of preliminary homogenization.

[0035] The homogenized magnesium-carbon containing materials are passed through a conventional crushing production line, part of which is crushed into 10-0mm granular aggregates, and part of which is ground into 180 mesh powder, which are all bagged for later use.

[0036] Next, add the bagged homogenized magnesium-carbon-containing aggregates and homogenized magnesium-carbon-containing fine powders into a 750 planetary mixer in the prescribed proportion, dry mix for 2 to 5 minutes, add the anhydrous cannon mud binder weighed in proportion in advance into the mixer at one time, wet mix for 5 to 10 minutes, and discharge the materials.

[0037] Install the mold on the electric brick press or friction brick press in advance. The length is generally 200-300mm, the width is 80-150mm, and the height is 50-100mm. Simply press the mud from the mixer into a fixed size of furnace bricks. After pressing the bricks, let them stand for 8-16 hours, and dry them in a drying kiln heated by electric heating or gas hot air. Close the door after entering the kiln, and raise the temperature from room temperature by 20-30℃ per hour to 120-150℃. Keep the highest temperature for 4-6 hours, turn off the fire, and cool to below 80℃ before leaving the kiln, picking and packaging, and shipping.

[0038] The raw material and finished product indicators of the magnesium-containing carbon-containing furnace repair bricks for the converter of the present invention are shown in Table 2.

[0039] Table 2

[0040]

[0041] Embodiment 1:

[0042] Recycling of 170 tons of carbon steel ladles from a steel plant. The types of refractory materials after use of the carbon steel ladles include waste magnesium carbon bricks from the slag line, waste aluminum magnesium carbon bricks from the bottom of the ladles, waste magnesium aluminum carbon bricks from the ladles wall, waste fire clay, waste steel slag, and various refractory metamorphic layers.

[0043] Example 1 The magnesium-containing carbon-containing bricks for the new converter bottom repair are composed of the following raw materials in weight percentage: 77% of mixed magnesium-containing carbon-containing aggregate particles of 10-0 mm, 23% of mixed magnesium-containing carbon-containing fine powder 180 mesh, and 5% of anhydrous taphole binder.

[0044] The production method is:

[0045] First, the carbon steel ladle is removed and the used refractory materials mixed and stored are simply homogenized. Specifically: According to the amount of homogenized used refractory materials, various mixed used refractory materials are shoveled out one by one on a flat site with a forklift, and then re-stacked layer by layer. Repeat this process 7 times to achieve the purpose of preliminary homogenization.

[0046] The homogenized magnesium-carbon-containing materials are passed through a conventional crushing production line, part of which is crushed into 10-0mm granular aggregates, and part of which is ground into 180-mesh powder, which is then bagged for later use.

[0047] Next, add the bagged homogenized magnesium-carbon-containing granular aggregate and homogenized magnesium-carbon-containing material powder into a 750 planetary mixer in the specified proportion, dry mix for 4 minutes, add the anhydrous cannon mud binder weighed in proportion in advance into the mixer at one time, wet mix for 8 minutes, and then discharge.

[0048] Install the mold on the electric brick press or friction brick press in advance. The length is generally 230mm, the width is 115mm, and the height is 50mm. Simply press the mud from the mixer into a fixed size of furnace bricks. After pressing the bricks, let them stand for 12 hours, and dry them in a drying kiln heated by electric heating or gas hot air. Close the door after entering the kiln, and raise the temperature from room temperature by 20℃ per hour to 150℃. Keep the highest temperature for 6 hours, turn off the fire, and cool to below 80℃ before leaving the kiln, picking and packaging, and shipping.

[0049] Example 1 The raw material and finished product indicators of magnesium-containing carbon-containing furnace repair bricks for converter are shown in Table 3.

[0050] Table 3

[0051]

[0052] Embodiment 2:

[0053] Recycling of 210 tons of carbon steel ladle from a steel plant. The types of refractory materials after use of the carbon steel ladle include waste magnesium carbon bricks from slag line, waste aluminum magnesium carbon bricks from ladle bottom, waste magnesium aluminum carbon bricks from ladle wall, waste fire clay, waste steel slag, and various refractory metamorphic layers.

[0054] Example 2 The magnesium-containing carbon-containing furnace bricks for the new converter bottom repair are composed of the following raw materials in weight percentage: the proportion of mixed magnesium-containing carbon-containing material aggregate particles 10-0mm is 73%, the proportion of mixed magnesium-containing carbon-containing material fine powder 180 mesh is 27%, and anhydrous cannon mud binder accounting for 5.2% of the total amount of mixed magnesium-containing carbon-containing materials.

[0055] The production method is:

[0056] First, the carbon steel ladle is removed and the used refractory materials mixed and stored are simply homogenized. Specifically: According to the amount of homogenized used refractory materials, various mixed used refractory materials are shoveled out one by one on a flat site with a forklift, and then re-stacked layer by layer. Repeat this process 7 times to achieve the purpose of preliminary homogenization.

[0057] The homogenized magnesium-carbon-containing materials are passed through a conventional crushing production line, part of which is crushed into 10-0mm aggregate particles, and part of which is ground into 180-mesh powder, which is then bagged for later use.

[0058] Next, add the bagged homogenized magnesium-carbon-containing aggregates and homogenized magnesium-carbon-containing fine powders into a 750 planetary mixer in the prescribed proportion, dry mix for 5 minutes, add the anhydrous cannon mud binder weighed in proportion in advance into the mixer at one time, wet mix for 10 minutes, and discharge the materials.

[0059] Install the mold on the electric brick press or friction brick press in advance. The length is generally 200mm, the width is 100mm, and the height is 35mm. Simply press the mud from the mixer into a fixed size of furnace bricks. After pressing the bricks, let them stand for 14 hours, and dry them in a drying kiln heated by electric heating or gas hot air. Close the door after entering the kiln, and raise the temperature from room temperature by 25℃ per hour to 150℃. Keep the highest temperature for 4 hours, turn off the fire, and cool to below 80℃ before leaving the kiln, picking and packaging, and shipping.

[0060] Example 2 The raw materials and finished product indicators of magnesium-containing carbon-containing furnace bricks for converters are shown in Table 4:

[0061] Table 4

[0062]

Claims

1. A short-process application method for waste refractory materials without sorting and separation process, characterized in that: The method is to use the used carbon-containing lining refractory of the ladle directly for preparing converter repair bricks after homogenization and crushing without going through the sorting and separation process and without removing waste slag impurities.

2. According to claim 1, a short-process application method for waste refractory materials without sorting and separation process is characterized in that: Specific methods include: 1) Remove the carbon lining refractory materials from the steel, do not sort them out, mix them all and then homogenize them; 2) crushing the mixed waste refractory material homogenized in step 1), crushing a part into particles less than 10 mm as aggregate, and grinding a part into 180 mesh powder; 3) The granular aggregate of less than 10 mm is mixed at a ratio of 70wt% to 80wt%, the powder of 180 mesh is mixed at a ratio of 20wt% to 30wt%, and an anhydrous taphole binder is added at a ratio of 3wt% to 6wt% of the total amount of the aggregate and the powder; 4) First, dry mix the aggregate and powder for 2 to 5 minutes, then add the anhydrous taphole mud binder at once, wet mix for 5 to 10 minutes, and then discharge; 5) Pressing the mixture obtained in step 4) into bricks.

3. According to claim 2, a short-process application method for waste refractory materials without sorting and separation process is characterized in that: The mixed waste refractory materials after homogenization were randomly sampled, and the chemical indicators were as follows: MgO: 40%-65%, Al2O3: 20%-45%, SiO2: 5%-15%, CaO: 3%-10%, C: 3%-5%, Fe: 0-5%; other impurities included Fe2O3 and MnO.

4. According to claim 2, a short-process application method for waste refractory materials without sorting and separation process is characterized in that: The method of pressing into bricks in step 5) comprises: letting the pressed bricks stand for 8 to 16 hours, drying in a drying kiln, raising the temperature from room temperature by 20 to 30° C. per hour to 120 to 150° C., keeping the highest temperature for 4 to 6 hours, turning off the fire, cooling to below 80° C. and then taking them out of the kiln.

5. According to claim 2, a short-process application method for waste refractory materials without sorting and separation process is characterized in that: The physical and chemical indicators of the anhydrous taphole mud binder are: anthracene oil greater than 50wt%, asphalt greater than 10wt%; specific gravity greater than 1.

35.

6. A short-process application method for waste refractory materials without sorting and separation process according to claim 1 or 2, characterized in that: The physical indicators of the converter repair brick are: room temperature compressive strength greater than 20MPa, room temperature flexural strength greater than 5MPa, and bulk density greater than 2.2g / cm 3 ; Chemical indicators are: MgO: 40%~65%, Al2O3: 20%~45%, SiO2: 5%~15%, CaO: 3%~10%, C: 3%~5%, Fe: 0~5%; other impurities include Fe2O3 and MnO.

7. The short-process application method of waste refractory materials without sorting and separation process according to claim 2 is characterized in that: The dimensions of the converter repair bricks are 200-300 mm in length, 80-150 mm in width and 50-100 mm in height.

Citation Information

Patent Citations

  • Method for recycling waste refractory materials

    CN107129311A

  • Converter quick repair method based on waste refractory material

    CN115161427A

  • Method for utilizing waste mgo-c brick

    JP2009132951A